2022
DOI: 10.22376/ijpbs/lpr.2021.11.4.l147-152
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Yoga on Quality of Life of Oral Healthcare Professionals during Covid- 19 Pandemic

Abstract: Yoga is a holistic approach to mental and physical health and is classified by the national institutes of health as a form of complementary and alternative medicine for human life. COVID 19 pandemic has impacted the quality of life of oral health care professionals. Our aim was to assess the effect of yoga on the quality of life of these professionals . Thirty participants (12 male/18 female) with a mean age 40.5 ± 2.5 years were prepared utilizing a 45-minute common yoga protocol module .All members went to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The one single-arm study of Divya et al [51] showed a statistically significant improvement of satisfaction with life in HCPs immediately after the program, and it continued to increase on day 40. The one single-arm study of Pandey et al [68] showed a significant statistical improvement in the total score of quality of life due to the MBI. Finally, no significant differences in pre-post intervention were observed in empathy in the study of Miyoshi et al [64].…”
Section: Mbis Effectivenessmentioning
confidence: 96%
See 4 more Smart Citations
“…The one single-arm study of Divya et al [51] showed a statistically significant improvement of satisfaction with life in HCPs immediately after the program, and it continued to increase on day 40. The one single-arm study of Pandey et al [68] showed a significant statistical improvement in the total score of quality of life due to the MBI. Finally, no significant differences in pre-post intervention were observed in empathy in the study of Miyoshi et al [64].…”
Section: Mbis Effectivenessmentioning
confidence: 96%
“…The program included information on the nature of mindfulness, meditation practices, and yoga exercises. The protocol applied in the study by Pandey et al [68] included yoga postures (Asanas), breathing regulation techniques (Pranayama), and meditation (Dhyana), which favor the achievement of a state of dissociation between oneself and disturbing thought or activities. The intervention carried out by Vajpeyee et al [71] combined yoga sessions (which include meditation and deep breathing exercises) and music sessions (the participants could choose the type of music they preferred, and/or listen to instrumental music by Pandit VM Bhatt).…”
Section: Y -Depression Y -Anxietymentioning
confidence: 99%
See 3 more Smart Citations